Nonlinear Control of a Satellite Electrical Power System Based on the Sliding Mode Control. (16th September 2013) - Mojallizadeh, Mohammad Rasool; Karimi, Bahram
Abstract : The power electronic interface between a satellite electrical power system (EPS) with a photovoltaic main source and battery storage as the secondary power source is modelled based on the state space averaging method. Subsequently, sliding mode controller is designed for maximum power point tracking of the PV array and load voltage regulation. Asymptotic stability is ensured as well. Simulation of the EPS is accomplished using MATLAB. The results show that the outputs of the EPS have good tracking response, low overshoot, short settling time, and zero steady-state error. The proposed controller is robust to environment changes and load variations. Afterwards, passivity based controller is provided to compare the results with those of sliding mode controller responses. This comparison demonstrates that the proposed system has better transient response, and unlike passivity based controller, the proposed controller does not require reference PV current for control law synthesis.